Crime and Violence in Older Adults: Findings From the 2002 to 2017 National Survey on Drug Use and Health. Issue 1 (January 2022) - Holzer, Katherine J.; AbiNader, Millan A.; Vaughn, Michael G.; Salas-Wright, Christopher P.; Oh, Sehun
Studies on criminal behaviors largely focus on youth and younger adults. While criminal engagement declines with age, the aging population and significant costs associated with older offenders warrant their increased clinical and research attention. The present study utilizes data from the 2002 to 2017 National Survey on Drug Use and Health to estimate the prevalence and explore the sociodemographic and psychosocial correlates of criminal behavior in adults aged 50 years and older. The overall prevalence of older adults engaging in criminal behaviors during this time was approximately 1.20%. There was no significant difference in crime involvement between adults aged 50 to 64 years and 65 years and older. Older individuals who committed crimes were more likely to be male and Black and earning low income. Criminality was also associated with use of illicit substances and depression as well as receipt of mental health treatment.